The Imami Shiite beliefs from the perspective of the orientalist (Journal of Imam Al-Kadhim College, 2023)
In this research, we will discuss the Imami Shiite beliefs mentioned by the French orientalist Yann Richard (in his book, which he called Shiite Islam (Beliefs and Ideologies).We will shed light on the beliefs of the Imami Shiites, and we will explain what the orientalist Jean Richard said about the doctrine of imamate and occultation. We will discuss the opinions of the orientalists and discuss their words according to the blessed Qur’anic verses that came in this regard, while citing the noble hadiths of the Prophet that support the doctrine of imamate and occultation, which were mentioned in Sunni and Shiite Imami sources.
Keywords: Keywords: Divine Religions, Islamic Encyclopedia, Cultural Heritage, Yann Richard